Aktivitas Antihipertensi dari Ekstrak Etanol Daun Dewandaru (Eugenia uniflora L.) pada Tikus Putih Jantan yang Diinduksi Adrenalin - Eka Umayasari; Lucia Vita Inandha Dewi; Mamik Ponco Rahayu (Jurnal Farmasi Indonesia, 2015)
Hypertension is a condition in which an individual develops above normal blood pressure, when systolic blood pressure exceeds 140 mmHg and diastolic exceeds 90 mmHg. Hypertension becomes health problem in the world. Dewandaru leaves contained flavonoid, saponin and tannin. This research aimed to find out the antihypertensive activity of dewandaru leaves ethanol extract and to find out the most optimum dose of dewandaru ethanol extract (Eugenia uniflora L.). Dewandaru leaves ethanol extract was obtained through extraction using maceration method and using ethanol 96% solvent. This study employed 25 male white rats divided into 5 groups: groups I (control with kontrol negatif, II (control with captopril), III (ethanol extract at 0.3 mg/200 gBW dose), IV (ethanol extract at 0.6 mg/200 g BW dose), V (ethanol extracts at 1.2 mg/200 g BW dose). The tested animal was made hypertensive with adrenaline induction intraperitoneally. The blood pressure measurement was conducted on the week-3 using blood pressure analyzed. The analysis used in this research was ANOVA with Dunnet T3 advanced test. From the result of research, it could be found that all doses of dewandaru leaves ethanol extract had antihypertensive activity. Dose 1.2 mg/200 g BW had effect equivalent to captopril’s.